2018
DOI: 10.12659/msm.910135
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Noninvasive Dynamic Indices of Fluid Responsiveness Among Different Ventilation Modes in Dogs Recovering from Experimental Cardiac Surgery

Abstract: BackgroundFluid resuscitation is a cornerstone of minimizing morbidity and mortality in critically ill patients, but the techniques for predicting fluid responsiveness is still a matter of debate. In this study, we aimed to evaluate the utility of noninvasive stroke volume variation (SVV), pulse pressure variation (PPV), and systolic pressure variation (SPV) as a dynamic predictor for assessing fluid responsiveness during different ventilation modes in anaesthetized, intubated dogs recovering from cardiac surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Previous studies have shown that SVV threshold values of 13.5-15% for a 10% SVI response in dogs undergoing cardiac surgery (73-83% sensitivity and 60-84% specificity) [16,17] are in agreement with the present study of dogs with PH receiving the inotropic support. These findings support the feasibility of EV at least in part, for assessing intraoperative fluid responsiveness in anesthetized mechanically ventilated dogs such as continuous/synchronized intermittent mandatory ventilation [18,21].…”
Section: Plos Onesupporting
confidence: 64%
See 2 more Smart Citations
“…Previous studies have shown that SVV threshold values of 13.5-15% for a 10% SVI response in dogs undergoing cardiac surgery (73-83% sensitivity and 60-84% specificity) [16,17] are in agreement with the present study of dogs with PH receiving the inotropic support. These findings support the feasibility of EV at least in part, for assessing intraoperative fluid responsiveness in anesthetized mechanically ventilated dogs such as continuous/synchronized intermittent mandatory ventilation [18,21].…”
Section: Plos Onesupporting
confidence: 64%
“…Although only a few studies have directly compared SVV with other estimates of dynamic indices [ 50 , 51 ], our present and preliminary data demonstrated that both pulse pressure variation (PPV) and systolic pressure variation (SPV) showed comparable performance in predicting fluid responsiveness to raise the SVI and CI in dogs receiving high-risk veterinary anesthesia [ 21 ]. The optimal threshold value for SVV to discriminate between responders and nonresponders in dogs anesthetized in a variety of clinical scenarios is still limited because many factors (e.g., type and depth of anesthesia, ventilation modes, heart-lung interaction, and comorbid cardiac failure, etc.)…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…New indices based on heart and lung interactions, known as "dynamic indices" were introduced and their superiority was demonstrated over the previous "static indices", such as central venous pressure (CVP) [8,27]. Examples of these new "dynamic" respiratory indices are the systolic pressure variation (SPV) [6,41], pulse pressure variation (PPV) [15,40,41], stroke volume variation (SVV) [41], pleth variability index (PVI) [40] and the collapsibility of the vena cava (cIVC) [16], which are all based on cardiac response in terms of SV and cardiac output variations, to interactions between the heart and lungs during mechanical ventilation or spontaneous breathing.…”
Section: Discussionmentioning
confidence: 99%
“…These indicators were based on the Frank–Starling theorem and heart–lung interactions during mechanical ventilation (Díaz et al., 2015; Zlicar et al., 2018). Goal‐directed fluid therapy can shorten hospital stays, decrease postoperative complications and death of patients, and improve prognosis (Sasaki et al., 2018; Saxena et al., 2015; Zecavati et al., 2014). Currently, SVV and pulse pressure variation, based on dynamic haemodynamic parameters, are widely applied.…”
Section: Discussionmentioning
confidence: 99%